1994
DOI: 10.1007/bf01541499
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle variation of women's interest in erotica

Abstract: Female respondents were given the opportunity to choose feature films for viewing. Choices were made on the basis of synopses and promotional videos. These materials projected (i) a focus on erotic, sexual events, (ii) romantic themes, (iii) action-packed violent drama, and (iv) hilarious comedy. Additionally, respondents evaluated the appeal of the projected films. Respondents' position in the menstrual cycle was then determined, with placement into one of seven 4-day phases. Measured in both choices and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The results were consistent with previous findings that used explicit sexual stimuli or response options which generally found higher levels of sexual sensitivity and responsiveness during the follicular Note: The total number of observations in the first and second halves does not necessarily match since participants receiving an installment near the middle of their cycle were placed into these categories based on their individual variations in their cycle. Also, some participants only completed four installments, resulting in empty cells phase of the cycle (e.g., Bullivant et al, 2004;Krug et al, 1994;Laeng & Falkenberg, 2007;Zillmann et al, 1994). The stable level of sexual interpretations across the cycle in the oral contraceptive users also matches past findings.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results were consistent with previous findings that used explicit sexual stimuli or response options which generally found higher levels of sexual sensitivity and responsiveness during the follicular Note: The total number of observations in the first and second halves does not necessarily match since participants receiving an installment near the middle of their cycle were placed into these categories based on their individual variations in their cycle. Also, some participants only completed four installments, resulting in empty cells phase of the cycle (e.g., Bullivant et al, 2004;Krug et al, 1994;Laeng & Falkenberg, 2007;Zillmann et al, 1994). The stable level of sexual interpretations across the cycle in the oral contraceptive users also matches past findings.…”
Section: Discussionsupporting
confidence: 80%
“…Bullivant et al (2004) reported increased sexual interest and more frequent sexual fantasies on days prior to and during the LH surge that occurs towards the end of the follicular phase. Zillmann, Schweitzer, and Mundorf (1994) found that, when given the choice between different genres of movies, women's choice of erotic films peaked during the ovulatory phase, and was at lowest levels during the beginning of the luteal phase. Similarly, women's dreams had more erotic content in the days before ovulation (Natale, Albertazzi, & Cangini, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Past research has established current mood state as a key factor for selective exposure to media especially for entertainment choices. 32,33 However, few of the available published studies on children's perception of stressful life events have examined perceptions of negative life events in relation to media consumption habits. This study investigates the generality of social compensation and mood management concepts by examining the relationship between these motives for Internet use and the upsetting experience of stressful life events.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The menstrual cycle has a profound effect on a woman's mating‐related desires, preferences, and behaviors. These include increases in sexual desires and activity (Adams, Gold, & Burt, 1978; Röder, Brewer, & Fink, 2009; Stanislaw & Rice, 1988; Wilcox, Weinberg, & Baird, 1995), response to sexual stimuli (Luschen & Pierce, 1972; Slob, Bax, Hop, Rowland, & van der Werff ten Bosch, 1996; Zillmann, Schweitzer, & Mundorf, 1994), and extra‐pair desires (Gangestad, Thornhill, & Garver‐Apgar, 2002; Haselton & Gangestad, 2006; Pillsworth & Haselton, 2006). Furthermore, numerous scholars have found that women's preferences for particular types of men change as a function of their menstrual cycles.…”
Section: The Effects Of the Menstrual Cyclementioning
confidence: 99%